2022
DOI: 10.3389/fcimb.2022.997875
|View full text |Cite
|
Sign up to set email alerts
|

How promising are HIV-1-based virus-like particles for medical applications

Abstract: New approaches aimed at identifying patient-specific drug targets and addressing unmet clinical needs in the framework of precision medicine are a strong motivation for researchers worldwide. As scientists learn more about proteins that drive known diseases, they are better able to design promising therapeutic approaches to target those proteins. The field of nanotechnology has been extensively explored in the past years, and nanoparticles (NPs) have emerged as promising systems for target-specific delivery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 167 publications
0
3
0
Order By: Relevance
“…To generate a delivery platform with the ability to target specific cells and to induce an antiviral response, we produced virus-like particles (VLPs) by using the well described HIV-1 system ( Arevalo et al., 2016 ; Martins et al., 2022 ) enveloped with VSV-G glycoprotein and incorporating a 5’ppp-RNA, termed M8, that triggers a type I IFN antiviral program upon binding to the RIG-I cytosolic sensor. As a negative control we used VLPs carrying CIAP-M8, in which the 5’ triphosphate group was removed from M8 by the Calf Intestinal Alkaline Phosphatase.…”
Section: Resultsmentioning
confidence: 99%
“…To generate a delivery platform with the ability to target specific cells and to induce an antiviral response, we produced virus-like particles (VLPs) by using the well described HIV-1 system ( Arevalo et al., 2016 ; Martins et al., 2022 ) enveloped with VSV-G glycoprotein and incorporating a 5’ppp-RNA, termed M8, that triggers a type I IFN antiviral program upon binding to the RIG-I cytosolic sensor. As a negative control we used VLPs carrying CIAP-M8, in which the 5’ triphosphate group was removed from M8 by the Calf Intestinal Alkaline Phosphatase.…”
Section: Resultsmentioning
confidence: 99%
“…We also compared the S-EABR construct to other eVLP approaches (Martins et al, 2022) that require co-expression of S protein with structural viral proteins, such as HIV-1 Gag (Hoffmann et al, 2020) or the SARS-CoV-2 M, N, and E proteins (Syed et al, 2021). Western blot analysis showed that purified S-EABR eVLP fractions contained at least 10-fold more S protein than eVLPs produced by co-expression of S and Gag or S, M, N, and E (Figure 1G), suggesting that S-EABR eVLPs assemble and/or incorporate S proteins more efficiently than the other eVLP approaches.…”
Section: Resultsmentioning
confidence: 99%
“…VLPs can assembled with proteins a wide variety of viruses such as human papilloma virus (HPV) [24], human immunodeficiency virus (HIV) [25], Norwalk virus [26], and influenza virus [27]. Moreover, VLPs can be constructed in different expression systems, namely prokaryotic (bacteria) [28], eukaryotic (plant cells [29], insect cells [30], yeast [31] and mammalian cells [32]) and cell-free platforms [33].…”
Section: Figure 1 Relevant Features Of Vlps For Biomedical Applicationsmentioning
confidence: 99%